Game design and development using GF engine - Thi, Chanh Hien (2014)
Game Factory (GF) Engine is a next-generation rapid game development platform, offering a customizable, reusable, interoperable and modular framework for both researchers and game designers. On top of that framework is a skeletal animation tool, called WaKu. Through 3D visualization and scene management, this animation tool is used to implement key-framed cut-out and flat articulated shadow puppet animation system.